In Situ Preparation of Mechanically Enhanced Hydrogel via Dispersion Polymerization in Aqueous Solution. Issue 18 (13th April 2021) - Chen, Honggui; Zhang, Xiang; Lin, Ziyu; Zhang, Rui; Yu, Bingran; Li, Yang; Xu, Fu‐Jian
Abstract: Hydrogels with improved mechanical properties can expand to a greater range of applications. The fabrication of conventional toughened hydrogels typically requires precise modifications, multiple components, and complex steps. Here, a straightforward "one‐step" polymerization method for the in situ preparation of hydrogels in aqueous solutions, is reported. Inspired by polymerization‐induced self‐assembly (PISA), water‐miscible monomers are copolymerized during the hydrogel fabrication; the growing blocks eventually form physical bridges thus providing a mechanism for effective energy dissipation. The rheological and mechanical properties are evaluated and the results reveal that this strategy can be an effective approach to design mechanically enhanced hydrogels for a wide range of applications. Abstract : This study reports a facile method for the in situ preparation of mechanically enhanced hydrogels. Hydrophobic interactions are introduced directly into the hydrogel during gelation by polymerization‐induced self‐assembly in aqueous solution, which provides an energy dissipation mechanism for the hydrogel. This strategy allows the hydrogel to have tunable and enhanced mechanical properties for a wide range of applications.